2020
DOI: 10.1111/acem.14080
|View full text |Cite
|
Sign up to set email alerts
|

Improving Follow‐up Attendance for Discharged Emergency Care Patients Using Automated Phone System to Self‐schedule: A Randomized Controlled Trial

Abstract: Background Automated phone appointment reminders have improved adherence with follow‐up appointments in a variety of hospital settings, but have mixed results in patients discharged from the emergency department (ED). Increasing adherence to follow‐up care has been a priority in the ED to improve patient outcomes and reduce unnecessary future visits. Methods We conducted a prospective randomized open, blinded end‐point (PROBE) trial of 278 adult patients discharged from the ED and referred to a provider for fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…Across delivery methods and formats, interventions to improve care transitions have been much more successful at improving outpatient clinical follow‐up or adherence behaviors/outcomes than ED re‐visitation, regardless of the time frame measured 15,20,21,40 . A 2020 meta‐analysis by Aghajafari et al, 20 involving 20 randomized controlled trials of ED‐based interventions for improving care transitions, found 79% increased odds of outpatient follow‐up overall, but no significant treatment effects on ED utilization or hospitalization.…”
Section: Discussionmentioning
confidence: 99%
“…Across delivery methods and formats, interventions to improve care transitions have been much more successful at improving outpatient clinical follow‐up or adherence behaviors/outcomes than ED re‐visitation, regardless of the time frame measured 15,20,21,40 . A 2020 meta‐analysis by Aghajafari et al, 20 involving 20 randomized controlled trials of ED‐based interventions for improving care transitions, found 79% increased odds of outpatient follow‐up overall, but no significant treatment effects on ED utilization or hospitalization.…”
Section: Discussionmentioning
confidence: 99%
“…Systematic quality improvement measures targeting the appropriateness of postendoscopy care and follow-up after an esophageal FBI should be considered. A previous trial showed that the use of an automated phone and text messaging system allowing patients to schedule follow-up appointments immediately after ED discharge resulted in a 25.9% improvement in follow-up adherence (25). Previous studies have also demonstrated that the incorporation of a standardized patient navigator, who helps guide patients through the health care system by communicating with other providers, setting up appointments, and accessing community resources, results in improved follow-up (26).…”
Section: Discussionmentioning
confidence: 99%